Estimation of agricultural energy efficiency in five provinces: based on data envelopment analysis and Malmquist index model. Issue 2 (15th June 2022) - Wen, Lei; Li, Huapeng
ABSTRACT: Based on the super-SBM model, this paper studies the agricultural energy efficiency of five provinces in China from 2004 to 2015. In addition, the Malmquist index is used for dynamic analysis of agricultural energy efficiency and to identify drivers of these changes. The results show that: (1) The inland provinces have lower agricultural energy efficiency than the wealthy eastern coastal provinces; (2) Technological progress is the most important factor affecting efficiency changes, and the provinces with lower efficiency are more likely to achieve greater improvements; (3) The energy efficiency of the provinces that are agricultural intensive areas is relatively low. Therefore, adjusting the agricultural production structure and emphasizing diversified agriculture will help improve the energy efficiency of agriculture. At the same time, it is necessary to strengthen agricultural cooperation among different provinces to jointly improve agricultural energy efficiency.